Analisis Financial Distress pada Bank Syariah di Indonesia Menggunakan Metode Classification and Regression Tree (CART) - Aguspri, Amellia (Jurnal Ilmiah Ekonomi Islam, 2024)
Using the Grover and Classification and Regression Tree (CART) techniques, this research aims to evaluate the factors that influence the financial conditions of Islamic banks from 2010 to 2021. The sample for this research was taken using a purposive sampling technique from five banks registered in OJK from 2010 to 2021. The results of this research using Grover analysis show that no bank has experienced bankruptcy with an accuracy value of 100%. On the other hand, according to decision tree regression using the Classification and Regression Trees (CART) method, FDR, NPM and CAR are the three factors that influence financial bankruptcy. And it is known that of the three ratios, FDR is the most significant.